Efektivitas Pola Latihan Teknik Dasar Sepak Sila dan Sepak Kura dalam Pembinaan Atlet Putra pada Tim Sepak Takraw di Universitas Palangka Raya - Razzi, Fahrul; Dony, Garry William; Hernando, Eko; Alamsyah, Iwan Noor; Abdullah, Abdullah (Universitas Hamzanwadi, 2026)
Problems in coaching novice sepak takraw athletes at the university level often lie in the lack of structured and measurable basic technique training patterns, which results in weak fundamental mastery. This study aims to analyze the effectiveness of applying systematic basic technique training patterns for sepak sila and sepak kura in improving the skills of novice athletes. The method used was a quasi-experiment with a one-group pretest-posttest design on 20 beginner athletes from the University of Palangka Raya. The research instrument was a validated skills test (Aiken's V validity > 0.80, reliability r > 0.85) to measure ball control, passing accuracy, defense, and attack. The structured training intervention was given for 6 weeks with a frequency of 3 times per week. The results of the paired sample t-test showed a significant increase in all skill aspects (p < 0.05), with an average score increase of between 16.2 and 17.2 points. The discussion relates these findings to motor learning theory, in which repetitive and gradual training strengthens motor memory and neuromuscular coordination. It is concluded that structured basic soccer and soccer training patterns are effective as a foundation for training beginner athletes.